(untitled) (Homoeopathy for All, 2024)
The Indian homeopathic pharma ceutical industry has undergone a remarkable transformation from its humble beginnings to becoming a well-established ecosystem today. Introduced in the early 19th century, homeopathy initially flourished in Bengal before spreading across In dia. Over time, the industry has wit nessed significant growth, with the market for homeopathic products projected to expand annually by 20- 25% and reach a substantial size of INR 20-30 billion. Despite the small market for homeopathic products other than drugs in India, the sec tor has shown resilience and steady progress.